DISCHARGE PLANNING STANDARD IN IMPROVING MOTHER'S SKILLS IN CARING FOR NEWBORN - Badrul Munif; Ninis Indriani; Nanik Nanik (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2020)
Background: Primipara is a client who really needs discharge planning to support her baby care skills independently at home after returning from the hospital. Discharge planning is one of the important elements in nursing services to improve client skills independently to perform care after discharge.Objectives: This study aims to determine the effectiveness of discharge planning according to the standards of maternal skills in caring for newborns.Methods: The research design was a quasi experimental study with a pre and post-test design with a control group. This research was conducted at a hospital in Banyuwangi. The research sample was 30 spontaneous primiparous patients, then divided into two groups, namely the experimental group given discharge planning according to the standard n=15 and the control group given conventional discharge planning treatment n=15. Sampling using Consecutive Sampling and data collection using the observation sheet of maternal skills about baby care. Data analyzed using paired T test and unpaired T test.Results: The results showed that the skills of mothers in caring for newborns in the experimental group had a higher value than the control group with the difference in the skills of caring for the umbilical cord of 3.60, changing diapers by 3.33 and breastfeeding by 6.60. Further analysis obtained p value=0.000 (p> 0.05), which means that there is a significant difference between the experimental and control groups.Conclusion: Discharge planning in accordance with standards can improve the skills of mothers in caring for their babies. Discharge planning in accordance with the standards should be implemented in the hospital, because discharge planning is one of the important elements in nursing services which aims to make clients independent after discharge from the hospital. Keywords: discharge planning, mother’s skill, caring, newborns